Bacterial Flora in the Sphenoid Sinus Changes with Perioperative Prophylactic Antibiotic Administration - BABA, Eiichi (Neurol Med Chir (Tokyo), 2021)
The complications of endonasal transsphenoidal surgery (ETSS) include meningitis and sinusitis, and these complications are troublesome. Some reports have investigated the type of bacteria and the susceptibility of sphenoid sinus mucosal flora to drugs. However, most specimens can be collected after perioperative antibiotic administration. In this study, 95 and 103 sphenoid sinus mucosal samples collected during ETSS from September 2013 to February 2015 and from June 2017 to January 2019, respectively, were examined for bacterial culture. Sphenoid sinus mucosal samples were collected after antibiotic administration in the first period, whereas samples were collected before antibiotic administration in the second period. Hence, the specimens in the second period were not affected by antibiotics. Moreover, drug susceptibility tests for the detected bacteria were performed. Overall, 52 and 51 bacterial isolates were collected during both periods. Gram-positive cocci (GPCs), including Staphylococcus aureus and Staphylococcus epidermidis, were more common in the non-antibiotic group than in the antibiotic group (p <0.01). However, the proportion of gram-negative rods (GNRs) did not significantly differ between the two groups (p = 0.54). The antibiotic group had a significantly higher proportion of bacteria resistant to ampicillin (p <0.01) and first-generation cephalosporin (p = 0.01) than the non-antibiotic group. In conclusion, there was a difference in bacterial flora in the sphenoid sinus mucosal samples collected before and after intraoperative antibiotic administration.